High throughput microwell spectrophotometric assay for olmesartan medoxomil in tablets based on its charge-transfer reaction with DDQ - Darwish Ibrahim A.; Wani Tanveer A.; Khalil Nasr Y.; Abdel-Rahman Hamdy M. (Acta Pharmaceutica)
The study describes the development and validation of a new microwell-based spectrophotometric assay for determination of olmesartan medoxomil (OLM) in tablets. The formation of a colored charge-transfer (CT) complex between OLM as an n-electron donor and 2,3-dichloro- -5,6-dicyano-1,4-benzoquinone (DDQ) as a p-electron acceptor was investigated, and employed as the basis for the development of the new assay. The proposed assay was conducted in 96-microwell plates. The absorbance of the colored-CT complex was measured at 460 nm with a microplate reader. Optimum conditions of the reaction and the analytical procedures of the assay were established. Under the optimum conditions, a linear relationship with a good correlation coefficient was found between the absorbance and the concentration of OLM in the range of 2-200 μg per well. The limits of detection and quantitation were 0.53 and 1.61 μg per well, respectively. No interference was observed from the excipients present in OLM tablets or from hydrochlorothiazide and amlodipine besylate that were co-formulated with OLM in some of its formulations. The assay was successfully applied to the analysis of OLM in tablets with good accuracy and precision. The assay described herein has a great practical value in the routine analysis of OLM in quality control laboratories, since it has a high throughput property and consumes low volumes of organic solvent. It thus offers a reduction in the exposure of analysts to the toxic effects of organic solvents, as well as a reduction in the cost of analysis.